ChemInform Abstract: Copper in Dendrimer Synthesis and Applications of Copper—Dendrimer Systems in Catalysis: A Concise Overview. Issue 28 (21st June 2013) - El Brahmi, Nabil; El Kazzouli, Said; Mignani, Serge; Bousmina, Mosto; Majoral, Jean Pierre
Abstract Review: 119 refs.